Johann Conrad Ulmers theologisches Vermächtnis: Seine fünf Predigten von den Heiligen Sakramenten, 1598 - Bryner, Erich (Zwingliana, 2024)
Johann Conrad Ulmer (1519-1600), a native of Schaffhausen, received his theological education in Basel, Strasbourg and Wittenberg. From 1543 to 1566 he worked as a preacher and reformer in Lohr am Main (Franconia), from 1566 to 1600 in Schaffhausen, first at the abbey church of All Saints, then in the church of St. John, and also as dean of the Schaffhausen parish. He was a highly respected and successful preacher, catechist, pastor, theological writer and church politician. His influence was so great that he is considered the second reformer and architect of the Reformed Church in Schaffhausen.He himself described his Five Sermons on the Holy Sacraments (1598) as his theological legacy. In them, he dealt with the sacraments in general, the Lord’s Supper in particular, the benefits, use and fruits of the Lord’s Supper, the misguided developments in the theology of the Lord’s Supper in the course of church history and their refutation by the Reformed theology of his time. He himself relied on the Bible, the Confessio Helvetica Posterior and other Reformed confessional writings. He polemicized sharply against the Roman Catholic and Lutheran churches, as laid down in the Council of Trent and the Formula Concordiae. Ulmer was strongly influenced by the confessional age that began in Schaffhausen around 1550.